Syringic acid protects retinal ganglion cells against H2O2-induced apoptosis through the activation of PI3K/Akt signaling pathway - Song, M; Du, Z; Lu, G; Li, P; Wang, L (Cellular and Molecular Biology, 2016)
Oxidative damage is believed to contribute to the pathogenesis of diabetic retinopathy. Syringic acid (SA), a naturally occurring O-methylated trihydroxybenzoic acid monomer extracted from Herba dendrobii, has been shown to possess antioxidant activity. However, the effects of SA on apoptosis of retinal ganglion cells (RGCs) induced oxidative damages have not yet been explored. The present study aimed to detect the effects of SA against hydrogen peroxide (H2O2)-induced cell damage in RGCs and to investigate the molecular mechanisms involved in this process. In the present study, we revealed that SA pretreatment obviously inhibited H2O2-induced RGC-5 cell injury. SA pretreatment also decreased H2O2-induced ROS production and MDA content in RGC-5 cells. In addition, SA pretreatment increased Bcl-2 expression and decreased the expression of Bax and cleaved caspase-3 in H2O2-induced RGC-5 cells. Moreover, SA pretreatment obviously increased PI3K and Akt phosphorylation in H2O2-induced RGC-5 cells. In conclusion, our results suggest that SA may protect RGC-5 cells against apoptosis induced by H2O2 through the activation of PI3K/Akt signaling pathway. Thus, SA may be beneficial in the treatment of diabetic retinopathy.